Red Seal landscape horticulturist identify plants and plant requirements. Line F Apply Horticultural Practices, F2 - Level 1,2,3 and 4 - Nakano, Michelle; BCcampus; BC Open Textbook Project (BCcampus, BC Open Textbook Project, 2020)
"Red Seal Landscape Horticulturist Identify Plants and Plant Requirements is an adaptation of KPU HORT 1155 Introduction to Plant Materials Lecture Notes. It is an editable, open access learning resource with interactive web-based experiences customized for horticulture students studying plant identification. This edition supports student achievement of the Level 1, 2, 3, and 4 learning goals for Red Seal Landscape Horticulturist Line F2"--BCcampus website.
This work is licensed under the Creative Commons Attribution CC-BY.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
Description based on online resource; title from html title page (viewed on October 19, 2020).
Keywords: Plants -- Identification; Horticulture; Electronic books